MODEL PENTAHELIK DALAM PENGEMBANGAN PARIWISATA DI KOTA SEMARANG - Yuningsih, Tri; Darmi, Titi; Sulandari, Susi (JPSI (Journal of Public Sector Innovations), 2019)
Objective The study describes the pentahelix model in tourism development in the city of Semarang. The problem is the lack of optimal cooperation between the actors involved. Theory uses the Policy Actor Theory and the Pentahelix Model. Descriptive research type, qualitative approach. Data is collected through: interview, observation and literature. Determination of informants with Snowball technique and key informants Head of the Department of Tourism and Culture of the city of Semarang. Data analysis by means of: data condensation, data verification and conclusion drawing. Data validation uses source triangulation. From the research it can be seen: (1) tourism development in Semarang city using pentahelix model, has involved academics, government, community, business, and mass media (2) Field findings are the Semarang City Tourism Promotion Agency (BP2KS) is not optimal and (3) Cooperation between the pentahelix model actors in the city of Semarang from the results of the research is not optimal. Research recommendations: revised the tourism regulation of Semarang city concerning "collaboration between actors, strengthening the institutional capacity of BP2KS, and subsequent researchers are advised to take the focus of research with different loci or make comparisons with the same focus.